2013
DOI: 10.1161/circulationaha.112.000311
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Onset-to-Reperfusion Time on Stroke Mortality

Abstract: Background-Onset-to-reperfusion time has been reported to be associated with clinical prognosis. However, its impact on mortality remained to be assessed. Using a collaborative pooled analysis, we examined whether early mortality after successful endovascular treatment is time dependent. Methods and Results-In a collaborative pooled analysis of 7 endovascular databases, we assessed the impact of onsetto-reperfusion time in large-artery occlusion (internal carotid artery or middle cerebral artery) on outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
122
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 23 publications
6
122
1
2
Order By: Relevance
“…[5][6][7][8][9][10][11] Also, the ORT in intra-arterial treatment was a main determinant factor in predicting favorable outcome. 3,4 Regarding collateral flow and ORT as determinant factors of favorable outcome, reperfusion of Ͼ300 minutes from onset in a poor collateral group was associated with decreased odds of clinical improvement and favorable outcome from a small retrospective cohort. 27 Our study also showed that ORT is a critical determinant of favorable outcome in a time-dependent fashion (each minute, 30 minutes, or reperfusion of Ͼ300 minutes were all associated with a decreased chance of favorable outcome).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] Also, the ORT in intra-arterial treatment was a main determinant factor in predicting favorable outcome. 3,4 Regarding collateral flow and ORT as determinant factors of favorable outcome, reperfusion of Ͼ300 minutes from onset in a poor collateral group was associated with decreased odds of clinical improvement and favorable outcome from a small retrospective cohort. 27 Our study also showed that ORT is a critical determinant of favorable outcome in a time-dependent fashion (each minute, 30 minutes, or reperfusion of Ͼ300 minutes were all associated with a decreased chance of favorable outcome).…”
Section: Discussionmentioning
confidence: 99%
“…and neuroradiologist (D.-H.K.) blinded to patient information and was dichotomized as poor (collateral-flow grades 0 -1) and good (2)(3)(4). 19 The coefficient for interobserver agreement was 0.864 for each collateral grade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was consistent with the findings of a previous study, which revealed an association between the time from onset to revascularization and a favorable clinical outcome and survival. 18 Given that no significant differences in the time from puncture to revascularization was identified between the groups, minimizing delays between stroke onset and hospital admission is a key factor for achieving good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a 30-min delay in the time until recanalization increases the incidence of early intracranial bleeding and mortality rate, and leads to poor outcomes. 21,22) Since the progression of neurological deficits may be rapid particularly in patients with ICO as described above, further shortening of the time is necessary. In this study, the procedure time was about 60 min, and the success rate using only the device as the first choice was about 50%.…”
Section: Discussionmentioning
confidence: 99%